E-LKPD Based on Ethnophysics "Siwalan Dawet Ice Making Process" to Improve High School Students' Learning Motivation - Anggita Rusmaya; Nadi Suprapto; Binar Kurnia Prahani; Eko Hariyono; Hanandita Veda Saphira (Studies in Philosophy of Science and Education, 2025)
Physics education often struggles to convey abstract concepts like static fluids, leading to low student interest and achievement. This study aims to develop an ethnophysics-based E-LKPD (Electronic Student Worksheet) that integrates physics with local culture, specifically the traditional process of making Siwalan dawet ice from Lamongan. The E-LKPD is designed to enhance learning motivation through an engaging, interactive edutainment approach. Using the ADDIE development model, only the Analyze, Design, and Development stages were conducted. This was due not only to time constraints but also because the research focused on product design and expert validation. Classroom implementation and evaluation were beyond the current research scope and are planned for future studies. Validation involved three expert lecturers who assessed presentation, content, and language using a Likert scale. Results indicated a very valid product, with an overall average score of 95.75% (presentation 91.75%, content 98.06%, language 97.22%). The E-LKPD was developed using the Liveworksheets platform, offering features like ElsQuiz, ElsAct, ElsLink, and ElsFo to promote interactivity and accessibility. Findings suggest that integrating ethnophysics and local culture into digital worksheets effectively improves student motivation in learning static fluid concepts.